Antecedents and consequences of work adjustment among self selecting expatriate academics in Malaysian public universities - Najihah Hanisah Marmaya (2013)
This study explores the work adjustment among self-selecting expatriate (SSE) in Malaysia. Specifically, this study examines the antecedents of expatriate academics' work adjustment and its influence on organizational commitment among expatriate academics in public universities in Malaysia within the context of Theory of Work Adjustment (JWA) by Dawis and Lofquist (1986), Dawis (2005). This empirical study attempts to enrich the understanding of the work adjustment, organizational commitment, individual adjustment, family adjustment, task and emotional satisfaction. The study concluded the analysis by testing the structural model that incorporated all of the hypothesized relationships in this research. A quantitative method was adopted in this study and responses from 251 expatriate academics in Malaysia were analyzed using Structural Equation Modeling (SEM). The result showed that most of the hypotheses were supported. This result show that expatriate academics are satisfied with their work environments when the needs that they possess related to work correspond with the reinforcements offered by their work environments. Emotional satisfaction was also found to link with work adjustment and work adjustment influence organizational commitment. However there was no correlation for abilities and ability requirement correspondence towards task satisfaction. Task satisfaction also does not relate to work adjustment. The most interesting finding is individual adjustment and Family adjustment support the moderating effect in this study. On the basis of the results of the thesis, it was concluded that expatriate academics with high satisfaction were able to adjust their work adjustment and increase their organizational commitment while working abroad. The result indicate that top management and Human Resource (HR) should focus on maintaining expatriates' satisfaction while on an international assignment as higher levels of work adjustment can positively influence organizational commitment. This result showed that the moderating effect in the model is revealed and can be applied among self-selecting expatriate in Malaysia.